Oscillatory natural convection of water‐glycerin mixture in a tall rectangular cavity: Transition to the chaos. Issue 8 (17th July 2018) - Al‐Rashed, Abdullah A.A.A.; Hassen, Walid; Aich, Walid; Kolsi, Lioua; Ayadi, Badreddine; Borjini, Mohamed Naceur
Abstract: This paper presents results of a numerical investigation involving bifurcation sequence leading to chaos in natural convection inside a vertically tall rectangular cavity having an aspect ratio equal to 15 and a Prandtl number equal to 125, corresponding to water‐glycerin mixture. The flow is characterized by a vertical stratification of the temperature field for Grashof numbers greater than or equal to 200 that is outside the conduction regime and it is stationary monocellular up to a critical value Grc  = 2800 where a periodic oscillatory regime appears. As Grashof number is increased, a transition from a steady periodic bicellular flow to an oscillatory multicellular flow, with 2 main central cells and 2 secondary cells, occurs. The regime remains periodic until Gr = 3100 where there is a first appearance of the chaotic regime which extends over a narrow interval of the Grashof number delimited by Gr = 3200.